1993
DOI: 10.1212/wnl.43.12.2632
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord MRI using multi‐array coils and fast spin echo

Abstract: We performed MRI of brain and spinal cord on 80 patients with multiple sclerosis (MS). Using multi-array coils and fast spin echo, 139 intrinsic lesions were identified in 59 patients (74%). Lesions were more common in the cervical than in the thoracic cord. Cross-sectional areas of the cord, measured from axial images at four levels, showed atrophy in 40%. Clinical disability correlated with cord atrophy but not with cord lesion load. These results show that the use of multi-array coils and fast spin echo all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
200
3
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(223 citation statements)
references
References 0 publications
15
200
3
5
Order By: Relevance
“…However, it has been demonstrated that findings on conventional MR scans do not always correlate well with the clinical status of the MS patients (41,42). In addition, previous studies did not find a correlation between the clinical disability of MS patients and the number and extent of the spinal cord lesions that were detected on MR (43)(44)(45)(46). Because DTI provides information about the microstructural WM organization, the resulting diffusion metrics are potentially more sensitive to detect spinal cord involvement in MS patients than conventional MR is.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, it has been demonstrated that findings on conventional MR scans do not always correlate well with the clinical status of the MS patients (41,42). In addition, previous studies did not find a correlation between the clinical disability of MS patients and the number and extent of the spinal cord lesions that were detected on MR (43)(44)(45)(46). Because DTI provides information about the microstructural WM organization, the resulting diffusion metrics are potentially more sensitive to detect spinal cord involvement in MS patients than conventional MR is.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, MR can also be useful in patients who do not have clinical spinal cord involvement, because asymptomatic spinal cord lesions are common in MS and uncommon in other WM disorders (2). However, the spinal cord lesion information as obtained by a conventional MR examination does not always correlate well with the clinical disability of the patient and/or with histological information (3)(4)(5). It has been demonstrated that the white matter (WM) regions that appear normal on conventional MR images, referred to as normal-appearing WM (NAWM), are also involved in the MS disease process (6 -8).…”
mentioning
confidence: 99%
“…[1][2][3] The detection of cord abnormality is diagnostically useful because silent cord lesions are rare in other neurologic disorders and in normal aging. 4 Since the integration of MR imaging into the International Panel (McDonald) criteria in 2001, 5 there is increasing international effort to standardize MR imaging protocols.…”
mentioning
confidence: 99%
“…Furthermore, images can be acquired using only a head coil. Just as importantly, much of the spinal cord pathology is reported to occur in the cervical cord (21,22), making it a relevant site for investigation. By utilizing these image analysis techniques longitudinally, studies have revealed a significant reduction in upper cervical cord CSA in both relapsing remitting (RR) and progressive MS over periods as short as six months (10).…”
mentioning
confidence: 99%